Unraveling the Role of Financial Attitude: A Key Moderator of Financial Literacy in Shaping Financial Behavior - Sahrian Putra*, Muhammad Rafli; Prajawati, Maretha Ika (JURISMA : Jurnal Riset Bisnis & Manajemen, 2023)
This research aims to examine the influence of financial literacy levels and financial attitudes on financial behavior and the moderating effect of the financial attitude variable. The study employed a questionnaire as a research method distributed to 75 respondents who are the organizers of the Investment Gallery of the Indonesia Stock Exchange at UIN Malang, UM, and Ma Chung University. The analysis technique used Partial Least Square. The research results indicate that financial behavior is positively influenced by the financial literacy level variable, although it is not significant. On the other hand, the financial behavior variable is significantly positively influenced by the financial attitude variable. Moreover, the financial attitude variable, as a moderating variable, has a positive impact on the relationship between the financial literacy level variable and the financial behavior variable. Keywords: Financial Literacy Level; Financial Attitude; Financial Behavior; Moderating Variable; Partial Least Square